Rancang Bangun Sistem Informasi Pengelolaan dan Monitoring Stok Barang Secara Real-Time : Studi Kasus: Gudang PT. Tirta Investama DC Jatiasih - Dyan Yuliana; Hendrawan A Jayadi (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
This study ims to analyze the implementation of a real-time inventory management system, identify challenges in the current inventory process, and provide appropriate solutions. Based on observations, inventory data management at PT. Tirta Investama still relies on manual and semi-computerized methods, resulting in inventory discrepancies, delays in information updates, difficulties in real-time monitoring, and inefficiencies in report generation and distribution processes. This research employed Library Research and Field Research methods. The system involves two user roles, namely Supervisors and Checkers. Supervisors are responsible for managing products, incoming and outgoing goods, transactions, and user accounts, while Checkers verify document consistency for goods processing activities. The system was developed using PHP Native and MariaDB version 10.4.27. The implementation of this system is expected to improve inventory monitoring in real time, enhance data accuracy, minimize recording errors, support faster decision-making in procurement and distribution activities, and facilitate more efficient report generation.